(untitled) (Revista Iberoamericana de Bioética, 2022)
Spiritual care is a core component in understanding how to provide palliative care. Nevertheless, the integration of spiritual support within a clinical setting has a long way to go. This study analyzes the design and evaluation process of a spiritual training program in a clinical setting, based on the needs of professionals providing pediatric palliative care in Spain. The development of skills and attitudes, and the acquisition of knowledge about spirituality in the health field can be facilitated through a training program that is geared towards practice, cultural context, and based on a theoretical framework of consensus with an interdisciplinary perspective.